Governance of the Volkswagen Group's Global Value Chain in Europe from 2019 to 2025 - Muhammad Nur Rahardiansyah Ramadhan; Swettie Ayu Calista; Thufailah Bilqiis; Adiasri Putri Purbantina (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2026)
This study examines the governance structure of the Volkswagen Group’s global value chain in Europe from 2019 to 2025. This period is marked by intensified environmental regulation in the European automotive sector, with stricter emission-reduction targets and accelerated decarbonization strategies. Existing research on Volkswagen’s supply chain focuses on operational efficiency, production systems, and technological innovation, but pays limited attention to how environmental regulatory pressure shapes value chain governance in advanced manufacturing, even though global value chain theory suggests that regulatory pressure typically encourages firms to reorganize production networks through relocation strategies. However, Volkswagen Group presents an anomaly, as its production network remains highly centralized in Europe despite increasing regulatory pressure in the region. To address this gap, the study analyzes how governance structures within Volkswagen’s value chain under regulatory requirements. The research uses a qualitative design based on content analysis of secondary data, which includes company reports, sustainability reports, press releases, and academic publications. The Global Value Chain governance framework guides the assessment of transaction complexity, codification capability, and supplier capability. Findings indicate that Volkswagen’s value chain governance is best characterized as modular. This is reflected in high transaction complexity through JIT systems and product differentiation, strong codification capability via standardized supplier requirements and digital communication systems, and high supplier capability among technologically advanced suppliers